Applying human centered design principles to climate services workshop - Giraldo, Diana; Zapata, Emmanuel; Ortiz, Berta (2023)
Two-day workshop – November 29th and 30th, 2023 (Nairobi, Kenya), focusing on the development process of the Climate Services playbook, following the Human-Centered Design principles. The workshop is tailored for use cases within EiA who are either presently engaged or planning to work with climate data and services. The playbook aims to be a comprehensive guide for CGIAR researchers and partners involved in the development of climate services projects, incorporating insights from use case studies within EiA.